The Role of Age, Education and Work of Mothers in The Incidence of Stunting for Toddlers Aged 24 – 59 Months - Haiya, Nutrisia Nu'im; Ardian, Iwan; Azizah, Intan Rismatul (Media Keperawatan Indonesia, 2021)
Stunting is a condition in which the afternoon z value is less than the standard deviation or when the child has a length or height that is not according to their age, There are various factors that affect the condition of stunting, but the mother is one of the most important factors in the occurrence of stunting, therefore this research was conducted with the aim of knowing the role or risk of maternal age, education and occupation in the incidence of stunting. This analytic observational study used a case-control design with a purposive sampling technique with a total of 106 respondents with each sample in each group being 53 for the case group and the control group also totalling 53 respondents. The chi-square test was defined as the test used in this study. In both groups, the majority of the test results were aged 20-35 years, the majority or most of them had high school education, and housewives made up the majority of occupations of the two groups. The results of this study indicate that the mother's age, education, and occupation are not related, but this study shows that mothers aged 20-35 years and with high school education have a lower risk of having a stunted child. Reflecting on this study, it can be seen that the ideal age and high maternal education cause mothers to be at lower risk of having stunted children.